Obstacles of Implementing Industry 4.0 in Nepalese Industries and Way-Forward - Devkota, Niranjan; Rajbhandari, Sharad; Poudel, Udaya Raj; Parajuli, Seeprata (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Industry 4.0 is buzzword in recent years and has become a topic of growing importance. It is a new technical framework that has been widely debated and studied and is likely to eventually constitute a fourth industrial revolution because it provides significant progress relevant to intelligent and potential industries in the market. As Nepal has introduced open policies for improving trade conditions in the mid-1980s, industries have to be competitive and capable enough to sustain themselves in such open policies. Such, dependencies can be minimize, and could only be possible, through the increasing the competitiveness of Nepalese industries with the help of use of new technologies. In such context, Nepalese industrial readiness for industry 4.0 is important topic to discuss. This study aims to identify the obstacles of implementing industry 4.0 in Nepalese Industries lies within 3 industrial estates of Kathmandu Valley i.e. Balaju, Patan and Bhaktapur industrial estates. Data has collected data from all 287 running industry from all three industrial estates with the help of questionnaire through respondent interview using KoBo Collect Toolbox. Our study finds that half of the industries (49%) face hurdles while adopting new technologies. Among them, the major hurdles are lack of infrastructure, lack of skilled manpower, lack of capital, poor implementation of policies. Among two third of the respondents think obstacles in implementing industry 4.0 is manageable. Political support, improvement in implementation mechanism and long term strategy are key factors that support industries to invest in new innovative technologies.